Time-to-degree and the business cycle - Dolores Messer; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2007)
When students themselves enjoy large degrees of freedom in determining the duration of their studies, it results in a fairly large degree of interindividual variance in terms of time-to-degree. This paper investigates individual time-to-degree in a model where students determine the optimum time-to-degree whilst weighing up the cost against the consumption benefit accruing from an additional semester of studies. According to this model, the cost level and consumption benefit depend, in turn, on the general economic environment during the study period. An empirical investigation using a data set based on Swiss university graduates from 1981 to 2001 shows that changes in the unemployment rate, real interest rate, wage levels, and economic growth have a significant impact on individual time-to-degree. These results are consistent with the conclusions derived from the theoretical model.
urn:nbn:de:101:1-20080401434
Keywords: 330; Bildungsverhalten; Bildungsabschluss; Zeit; Konjunktur; Schweiz